Conditional expression of Pomc in the Lepr-positive subpopulation of POMC neurons is sufficient for normal energy homeostasis and metabolism - Lam, Daniel D. (2015)
Peptides derived from the proopiomelanocortin (POMC) precursor are critical for the normal regulation of many physiological parameters, and POMC deficiency results in severe obesity and metabolic dysfunction. Conversely, augmentation of central nervous system melanocortin function is a promising therapeutic avenue for obesity and diabetes but is confounded by detrimental cardiovascular effects including hypertension. Because the hypothalamic population of POMC-expressing neurons is neurochemically and neuroanatomically heterogeneous, there is interest in the possible dissociation of functionally distinct POMC neuron subpopulations. We used a Cre recombinase-dependent and hypothalamus-specific reactivatable PomcNEO allele to restrict Pomc expression to hypothalamic neurons expressing leptin receptor (Lepr) in mice. In contrast to mice with total hypothalamic Pomc deficiency, which are severely obese, mice with Lepr-restricted Pomc expression displayed fully normal body weight, food consumption, glucose homeostasis, and locomotor activity. Thus, Lepr+ POMC neurons, which constitute approximately two-thirds of the total POMC neuron population, are sufficient for normal regulation of these parameters. This functional dissociation approach represents a promising avenue for isolating therapeutically relevant POMC neuron subpopulations.